MAGNETIC MARKERS OF CRYSTALLINE BASEMENT STRUCTURE OF MIDDLE POBUZHYA (ON EXAMPLE OF GAIVORON-ZAVALLYA REGION) - SUKHORADA, A.; RESHETNYK, M.; KHOMENKO, R. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
The complex magetic exploration for studying rocks of granulitic complex of Average Pobugge the Ukrainian shield is submitted. An anomalous magnetic field is produce the garnet-quartz- magnetite rock with high magnetic characteristics.